2009
DOI: 10.1177/1045389x09347018
|View full text |Cite
|
Sign up to set email alerts
|

Development, Characterization, and Design Considerations of Ni19.5Ti50.5 Pd25Pt5 High-temperature Shape Memory Alloy Helical Actuators

Abstract: Shape memory alloys (SMAs) have been used in various applications since their discovery. However, their use as actuation devices in high-temperature environments has been limited due to the temperature constraints of commercially available materials. Recently, SMAs that produce good work characteristics at elevated temperatures have been developed at NASA’s Glenn Research Center. One such alloy, Ni19.5Ti50.5Pd25Pt 5, has shown repeatable strain recovery on the order of 2.5% in the presence of an externally app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…But very recently, additions of Pd and Pt have attracted extra attention compared with other alloying elements, since many favorable attributes of binary TiNi, such as high work output, ductility and workability, can be maintained to a reasonable extent in these ternary alloys [11][12][13][14][15]. In terms of transformation temperatures, TiNiPd alloys are capable of martensitic transformations up to 773 K (500°C).…”
Section: Introductionmentioning
confidence: 99%
“…But very recently, additions of Pd and Pt have attracted extra attention compared with other alloying elements, since many favorable attributes of binary TiNi, such as high work output, ductility and workability, can be maintained to a reasonable extent in these ternary alloys [11][12][13][14][15]. In terms of transformation temperatures, TiNiPd alloys are capable of martensitic transformations up to 773 K (500°C).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of pre-strain or ''training'' has long been recognized in the shape-memory actuator field [9][10][11][12][13][14][15]. These references indicate that there are optimal combinations of thermomechanical processing with subsequent prestraining (straining over that of the application) that tends to stabilize the microstructures for either stress or strain cycling.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the Young's modulus for NiTi alloys decreases with temperature reaching a significant minimum at about the start of the reverse transformation followed by a steep increase once the reverse transformation is completed. [44][45][46][47] The Ni 49.9 Ti 50.1 alloy studied here exhibits similar compliance characteristics that were measured using a dynamic technique 48 and would definitely provide a mechanism for reverse reorientation to occur with increasing temperature.…”
Section: -3mentioning
confidence: 54%